1985
DOI: 10.1029/wr021i004p00563
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatial Structure of Properties of Selected Aquifers

Abstract: Data from 31 regional aquifers are analyzed to identify the horizontal spatial correlation structure of transmissivity, hydraulic conductivity, and storage coefficient. Three parameters are estimated: the variance of small-scale variability (or nugget) and the variance and integral scale (range) of an exponential covariance function. The assumption of normality of the aforementioned geohydrologic parameters and their logarithmic transformations is also examined. Results are obtained which indicate that the log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(216 citation statements)
references
References 24 publications
8
206
1
1
Order By: Relevance
“…However, recent analyses of hydraulic conductivity data (Bakr, 1976;Byers and Stephens, 1983;and Hoeksema and Kitanidis, 1985) showed that although the hydraulic conductivity values vary significantly in space, the variation is not entirely random, but correlated in space. Such a correlated nature implies that the parameter values are not statistically independent in space and they must be treated as a stochastic process, instead of a single random variable.…”
Section: Statistical Representation Of Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent analyses of hydraulic conductivity data (Bakr, 1976;Byers and Stephens, 1983;and Hoeksema and Kitanidis, 1985) showed that although the hydraulic conductivity values vary significantly in space, the variation is not entirely random, but correlated in space. Such a correlated nature implies that the parameter values are not statistically independent in space and they must be treated as a stochastic process, instead of a single random variable.…”
Section: Statistical Representation Of Heterogeneitymentioning
confidence: 99%
“…For instance, Law (1944) and Bennion and Griffiths (1966) reported that the distribution of porosity data in an aquifer is normal. Hoeksema and Kitanidis (1985) suggested that the spatial distribution of storage coefficient may be log-normal. Hydraulic conductivity distributions (Figure 2) are usually reported to be log-normal (Law, 1944;Bulness, 1946;Warren et al, 1961;Bakr, 1976;Freeze, 1975;and Sudicky, 1986) or other (Jensen et al, 1987).…”
Section: Statistical Representation Of Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Farthing et al [22] presented results for di↵erent porous media scenarios by using di↵erent types of sands. It has been shown [11,29,48] that although the permeability values can exhibit large spatial variations, these variations are not entirely random but spatially correlated. Previously, such fields have been modelled using a log-normal distribution assumption [39].…”
Section: Letmentioning
confidence: 99%
“…For modelling the correlation of Z, i.e., expression (21), we use the following exponential covariance function [29,54,14,13]:…”
Section: Generation Of Random Permeability Fieldsmentioning
confidence: 99%